Effect of alfalfa, concentrate and ryegrass diets on guinea pig production variables - Herrera, H. (2024)
The present research evaluates the productive performance of guinea pigs fed with two different feed rations. Three groups of 15 male Peruvian guinea pigs were formed, each with three repetitions of five individuals. The guinea pigs in the control group (T0) were fed only with alfalfa, the first treatment group was fed with a combination of alfalfa and concentrated feed in a 3:1 ratio, respectively (T1), and the second experimental group was fed with ryegrass and the same balanced supplement, also in a 3:1 ratio (T2). At the end of the nine-week study, the average live weights obtained were 917.67 g in T0, 948.13 g in T1, and 911.60 g in T2. The average feed intake based on dry matter per guinea pig/day was increased gradually, with lower quantities for the group of guinea pigs fed only with alfalfa and higher quantities for the group of guinea pigs fed with ryegrass and concentrated feed. The feed conversion was better in T1 compared to the other two groups (p = <0.001). It is concluded that guinea pigs fed with alfalfa and supplemented with concentrated feed show greater weight gain.